Chemoresistance: Intricate Interplay Between Breast Tumor Cells and Adipocytes in the Tumor Microenvironment - Mentoor, Ilze; Engelbrecht, Anna-Mart; van Jaarsveld, Paul J.; Nell, Theo (Frontiers in Endocrinology, 2018)
Abstract Excess adipose tissue is a hallmark of an overweight and/or obese state as well as a primary risk factor for breast cancer development and progression. In an overweight/obese state adipose tissue becomes dysfunctional due to rapid hypertrophy, hyperplasia, and immune cell infiltration which is associated with sustained low-grade inflammation originating from dysfunctional adipokine synthesis. Evidence also supports the role of excess adipose tissue (overweight/obesity) as a casual factor for the development of chemotherapeutic drug resistance. Obesity-mediated effects/modifications may contribute to chemotherapeutic drug resistance by altering drug pharmacokinetics, inducing chronic inflammation, as well as altering tumour-associated adipocyte adipokine secretion. Adipocytes in the breast tumour microenvironment enhance breast tumour cell survival and decrease the efficacy of chemotherapeutic agents, resulting in chemotherapeutic resistance. A well know chemotherapeutic agent, doxorubicin, has shown to negatively impact adipose tissue homeostasis, affecting adipose tissue/adipocyte functionality and storage. Here, it is implied that doxorubicin disrupts adipose tissue homeostasis affecting the functionality of adipose tissue/adipocytes. Although evidence on the effects of doxorubicin on adipose tissue/adipocytes under obesogenic conditions are lacking, this narrative review explores the potential role of obesity in breast cancer progression and treatment resistance with inflammation as an underlying mechanism. Word count: 193